Microcellular morphology evolution of polystyrene/thermoplastic polyurethane blends in the presence of supercritical CO2. Issue 3 (May 2019) - Qu, Zhongjie; Mi, Jianguo; Jiao, Yang; Zhou, Hongfu; Wang, Xiangdong
In this article, a facile melt blending and solid batch foaming approach was proposed to prepare microcellular polystyrene/thermoplastic polyurethane (PS/TPU) blending foams with supercritical carbon dioxide (CO2 ). Compared with those of pure PS and pure TPU, an interesting phenomenon about the enhanced complex viscosity and storage modulus, as well as decreased loss factor of PS/TPU blends, was found. The solubility of CO2 in the PS/TPU blends was enhanced, owing to the CO2 solubilization effects of TPU. An interesting bimodal cell structure (BCS) was observed in the PS/TPU blending foams with the TPU content of 10, 15, and 20%. Consequently, a significant conclusion could be speculated that the generation of BCS in the PS/TPU blending system depended on not only the viscosity and morphology of the polymer blends but also the solubility and diffusivity of the CO2 as well as the type of cell nucleation. The thermal insulation property of PS foam was improved by the introduction of TPU.